Insect pollinators of oil palm plantations in South Sumatra, Indonesia - SITI HERLINDA; JELLY MILINIA PUSPITA SARI; WEI HONG LAU; ERISE ANGGRAINI; CHANDRA IRSAN; DELLANIA EKA RINDIANI; NOVRI NELLY; LISNAWITA LISNAWITA; RADIX SUHARJO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Herlinda S, Sari JMP, Lau WH, Anggraini E, Irsan C, Rindiani DE, Nelly N, Lisnawati, Suharjo R. 2025. Insect pollinators of oil palm plantations in South Sumatra, Indonesia. Biodiversitas 26: 5595-5611. Information on insect pollinator species of oil palm is crucial for management strategies that support sustainable production. This study aimed to identify pollinator insect species found in South Sumatra, Indonesia, and analyze their species diversity and abundance. Pollinators were sampled from male and female inflorescences at four time intervals (08:00-09:59 a.m., 10:00-11:59 a.m., 02:00-03:59 p.m., and 04:00-05:59 p.m.) using anthesis-based collection methods. The result showed that Elaeidobius kamerunicus and Elaeidobius spp. were the most common insect pollinators in oil palm production areas, occurring from lowland to midland regions. These species were present on both male and female inflorescences but were more abundant on male inflorescences, with peak activity recorded between 8:00 a.m. and 11:59 a.m. Apis mellifera and A. dorsata were also observed on both male and female inflorescences, though their activity was generally limited to the morning and midday periods. All species (E. kamerunicus, Elaeidobius spp., A. mellifera, and A. dorsata) are potential pollinators, as their visitation of both male and female inflorescences facilitates pollen transfer to the female flowers. Considering the continuous activity of E. kamerunicus and Elaeidobius spp. throughout the day, the use of contact insecticides in oil palm plantations should be avoided to reduce adverse impacts on pollinator populations. These findings provide baseline data for designing pollinator-friendly management practices in Indonesia's oil palm sector.